HUBUNGAN KUALITAS TIDUR TERHADAP MOTIVASI BELAJAR MAHASISWA BIMBINGAN DAN KONSELING ANGKATAN 2021 DAN 2022 - Nugroho, Sulis Wahyu; Rasimin, R; Harahap, Nur Hasanah (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2024)
This research aims to determine the relationship between sleep quality and learning motivation of Guidance and Counseling students class of 2021 and 2022. The approach in this research uses a quantitative approach with a correlation method. The sampling technique used simple random sampling with a sample size of 80 Guidance and Counseling student respondents from the class of 2021 and 2022. Based on the research results, a significance value of 0.000 0.05 was obtained and the r value was r table or -0.675 0.2172. So Ho is rejected, which means there is a significant relationship between sleep quality and learning motivation for Guidance and Counseling students from the class of 2021 and 2022.